The effectiveness of collaborative care delivered via telehealth in a pediatric primary care population - Vanderwood, Karl; Joyner, Jian; Little, Virna (Frontiers in Psychiatry, 2023)
Introduction: The prevalence of mental health conditions among children and adolescents in the United States has become a pressing concern, exacerbated by the COVID-19 pandemic. Collaborative care is an evidence-based model for identifying and treating depression and anxiety in healthcare settings, with additional promise for remote healthcare delivery. This study aims to evaluate the impact of a telehealth collaborative care model for adolescents with depression and anxiety in pediatric and primary care settings.Methods: Secondary analysis was conducted using de-identified national data from Concert Health, a behavioral health medical group offering remote collaborative care across 17 states. Baseline, 90-day, and 120-day assessments of the PHQ-9 and GAD-7 were collected, along with baseline covariates.Stepwise regression analysis was performed to determine the contribution of select covariates to improvement rates.Results: Among the analyzed data, 263 participants had complete PHQ-9 data, and 230 had complete GAD-7 data. In both the PHQ-9 and GAD-7 groups, over 50% of patients experienced treatment success based on success at discharge, as well as 90-and 120-day improvement rates. Predictors of success at discharge for the GAD-7 group included age at enrollment (OR 1.2258, 95% CI 1.01-1.496), clinical touchpoints (OR 1.1469, 95% CI 1.086-1.218), and lower baseline GAD-7 score (OR 0.9319, 95% CI 0.874-0.992). For the PHQ-9 group, Medicaid was significantly associated with not achieving a 50% reduction in PHQ-9 score at 120 days (OR 0.5874, 95% CI 0.349-0.979) Discussion: Collaborative care has demonstrated its effectiveness in treating adolescent populations, providing an opportunity to expand access to evidence-based behavioral health treatment for young individuals. Notably, collaborative care is already integrated into the Medicaid fee schedule for 22 states and accepted by all commercial payers. Given that individuals often turn to their trusted primary care providers for behavioral health care, offering collaborative care to adolescents can play a crucial role in addressing the ongoing mental health crisis.